American Serengeti : the last big animals of the Great Plains - Flores, Dan L. (Dan Louie), 1948- (University Press of Kansas, 2016)
"Bison. Horses. Coyotes. Wolves. Grizzly Bears. Pronghorns. A la John McPhee and Edward Hoagland, noted Western and environmental historian Flores dazzles with his vivid, informed, and richly detailed essays on six iconic animals of the American Great Plains. Diving into their genetic past as far back as the Pleistocene epoch and on up to restoration efforts in recent times, Flores is especially evocative and illuminating about the lives of these animals (and their interactions with humans) in the several centuries running from the dawn of the Age of Exploration through the end of the Indian Wars"--